Assessment of anticancer effect of chlorin e6 dimethyl ether for photodynamic therapy - M. A. Kaplan; V. P. Zorin; A. I. Malygina; I. V. Kashirtseva; L. M. Arkhipova (Biomedical Photonics, 2014)
Results of the study for anticancer efficacy of photodynamic therapy with chlorin e6 dimethyl ether for treatment of outbread rats with sarcoma M-1 are represented. The drug was given intravenously or intraperitonealy at a dose of 1.25 mg/kg body weight (light dose – 300 J/cm2) or 2,5 mg/kg body weight (light dose – 150 J/cm2). The spectrometry showed that maximal drug accumulation in tumor was in 2 h after intravenous injection or 3 h after intraperitoneal injection of photosensitizer, thus, sensitized tumors were irradiated according to these time intervals. Intraperitoneal injection of chlorin е6 dimethyl ether at a dose of 1.25 mg/kg body weight with treatment session in 3 h and light dose of 300 J/cm2 was the most effective (the complete response in animals – 86%).